A noção de variável em livros didáticos de Ensino Fundamental: um estudo sob ótica da organização praxeológica - Cruz, Eliana da Silva (2005)
The aim of this paper is to investigate how the notion of variable has been considered in Brazilian schoolbooks directed to students from the 1st. to the 8th educational degrees (usually from 7 to 15 years). The study intends to answer the following research question: How schoolbooks bring up the notion of variable having in view Chevallard s praxis organization? For this purpose, we developed a qualitative and documental analysis of four schoolbooks collections from the 5th to the 8th educational degrees. This analysis has been based on four aspects that we consider significant for the exposed study: first, we analyzed the way the schoolbooks are incorporating the orientation given by the National Curricular Parameters (PCNs), since they reported that they are in accordance to these proposals; next, we verified the authors approaches to introduce and develop Algebra and, finally, we studied the different applications given to the idea of variable. The research has been based on Chevallard s Anthropological Theory (1991), making use of an adaptation of the Praxis Organization proposed by the author. We have tried to identify, in the exercises that regard each aspect, which is the type of the task proposed, which is the way to accomplish this task, which is the technique involved and which is the theoretical-technologic argument behind this technique. We noticed that, though the schoolbooks present several Algebra conceptions and have been considering variables under different approaches, the predominance of the exercises for the application of the techniques still subsists